Thyroid Dysfunction and Autoantibodies Association with Hypertensive Disorders during Pregnancy - Azin Alavi; Khadijeh Adabi; Sepideh Nekuie; Elham Kazemi Jahromi; Mehrdad Solati; Alireza Sobhani; Hoda Karmostaji; Alireza Shahab Jahanlou (Hindawi Limited, 2012)
Background. Thyroid dysfunction and autoimmunity are relatively common in reproductive age and have been associated with adverse health outcomes for both mother and child, including hypertensive disorders during pregnancy. Objective. To survey the relation between thyroid dysfunction and autoimmunity and incidence and severity of pregnancy-induced hypertensive disorders. Method. In this case control study 48 hypertensive patients in 4 subgroups (gestational hypertension, mild preeclampsia, severe preeclampsia, eclampsia) and 50 normotensive ones were studied. The samples were nulliparous and matched based on age and gestational age and none of them had previous history of hypertensive or thyroid disorders and other underlying systemic diseases or took medication that might affect thyroid function. Their venous blood samples were collected using electrochemiluminescence and ELISA method and thyroid hormones and TSH and autoantibodies were measured. Results. Hypertensive patients had significant lower T3 concentration compared with normotensive ones with mean T3 values 152.5±48.93 ng/dL, 175.36±58.07 ng/dL respectively. Anti-TPO concentration is higher in control group 6.07±9.02 IU/mL compared with 2.27±2.94 IU/mL in cases. Conclusion. The severity of preeclampsia and eclampsia was not associated with thyroid function tests. The only significant value was low T3 level among pregnancy, induced hypertensive patients.